The comparative effects of diethyldithiocarbamate-copper complex with established proteasome inhibitors on expression levels of CYP1A2/3A4 and their master regulators, aryl hydrocarbon and pregnane X receptor in primary cultures of human hepatocytes - Vrzal, Radim; Dvorak, Zdenek (Fundamental & clinical pharmacology, 2016)
In the recent years, a therapeutic potential of disulfiram (Antabuse) complex with copper, as an anticancer drug, was recognized towards several cancer cell lines. The proteasome was suggested as one of the cellular targets for this compound. As the therapeutic use of diethyldithiocarbamate-copper complex (CuET) is expected to increase, it is of great interest to know whether this compound may be the source of drug-drug interactions via the induction of biotransformation enzymes, especially cytochromes P450 (CYPs). To this purpose, we examined the effect of CuET and compared it with typical inducers (rifampicin and dioxin) of CYPs and with well-established proteasome inhibitors (MG132 and bortezomib). Diethyldithiocarbamate-copper complex revealed inconsistent and rather modulatory effect on the expression of CYP1A2 and CYP3A4 in several cultures of human hepatocytes. Moreover, it was able to cause neither ubiquitin accumulation nor significant and dose-dependent inhibition of proteasome activity. It had no effect on essential transcription factors involved in regulation of selected CYPs, aryl hydrocarbon (AhR) nor pregnane X receptor (PXR). However, the AhR protein was increased in majority of examined hepatocyte cultures. The main finding of this study is that: (i) disulfiram-copper complex is not the cause of drug-drug interactions via CYP1A2/3A4 induction; (ii) proteasome inhibitors may have different impact on studied parameters in given in vitro system.
Keywords: dospělí; steroidní receptory; Cells, Cultured; Transcription Factors; Humans; lidé středního věku; transkripční faktory; Middle Aged; cytochrom P-450 CYP3A; mužské pohlaví; Cytochrome P-450 CYP3A; Hydrocarbons; cytochrom P-450 CYP1A2; Proteasome Endopeptidase Complex; Adult; Cytochrome P-450 CYP1A2; proteasomový endopeptidasový komplex; Hepatocytes; lékové interakce; měď; Copper; kultivované buňky; inhibitory proteasomu; hepatocyty; ženské pohlaví; Female; dithiokarb; lidé; Ditiocarb; Receptors, Steroid; Drug Interactions; Proteasome Inhibitors; Aged; senioři; Male; uhlovodíky